An anthropometric study on the primary school in a rural area of district Bareilly - Gupta, Dharmendra Kumar; Maheshwari, Sonam; Gupta, Shyam Bihari; Shrotriya, Ved Prakash; Singh, Atul Kumar; Kumar, Asheesh; Sinha, Ratnesh (International Journal of Health, 2015)
Now a day underweight as well as overweight has become serious problem among children and adolescents in developed and developing countries. Careful assessment, monitoring and follow up of these children and adolescent were of great importance for the health state of society. The aim of the present study was to determine the prevalence of obesity, overweight and underweight among primary school children in a rural area of district Bareilly. This cross-sectional study was performed on school-age children 4 to 14 years old, took place between December 2014 and March 2015.A total of 340 children (229 boys and 111 girls) were interviewed and examined. A pre-designed and pre-tested questionnaire was used to interview the study participants to elicit information on family characteristics like residence, religion, education and occupation of parents; and information on individual characteristics like age, sex. Anthropometric measurements were taken and noted by trained field workers. The prevalence of obesity, overweight was higher in boys than girls. There was significant relationship between BMI with gender and with age. Conclusion: Based on the results, although underweight was still relatively common in 4-14 year old children. Establishing interventional measures in order to prevent risky behaviors leading to Underweight and overweight seems to be highly necessary.